Strategies to modify the voluntary intake and feed selection in grazing small ruminants - Mazorra, C.; Fontes, Dayam?; Cubillas, Nieves; de Vega, A. (Cuban Journal of Agricultural Science, 2009)
Different elements that should be considered by producers of small ruminants are discussed to attain the efficient management of grazing herds. Outstanding aspects are dealt with such as those related to voluntary intake, diet selection, and understanding of the consequences of post-ingestion, the anatomic and physiological differences of the digestive tract between the species of small ruminants and their relationship with ingestion habit. Also, several management or strategies or practices using these concepts are described with the aim of modifying the voluntary intake and the feed selection of these animals. Among them, there is mention to the development of abilities to harvest the type of pasture or forage, the previous adaptation to the feed intake and the understanding of the consequences of the post-ingestion, the intake of feed or other nutritive substances in a form prior to the grazing, the use of the antiquality factors and other products to preserve plant sin paddocks, as well as the circuits of grazing, the diversity of species of ingested plants, the antiparasite effects and the mixed grazing. It was concluded that the knowledge and management of the different factors interacting in the processes of diet, intake and selection in grazing small ruminants allow producers to optimize the productive performance of their animals and attain the utmost sustainable handling of the production system, leading to the stability and persistence of the cattle ecosystems in Cuba. Key words: sheep, goat, feed selection, preference, aversion.